Penerapan Work At Office dan Work From Home dalam Mencapai Kinerja di Era Pandemi Covid-19 pada Bpjamsostek Pasuruan Pandaan - Zakky Ibrahim; Ernani Hadiyati; Umi Muawanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of the scheme for working from home in both the government and private sectors is one of the consequences of the PSBB (Working from Home/WFH). BPJamsostek plans to implement Work At Office (WAO) by complying with health protocols, and also implements Work From Home (WFH) to support activities during the Covid-19 pandemic. Based on a case study at BPJamsostek Pandaan Branch which has implemented Work At Office (WAO) and Work From Home (WFH) in the Covid-19 Pandemic Era, the author focuses on employee performance achievements by implementing Work At Office (WAO) and Work From Home ( WFH). The aim of this research is to determine the implementation and performance achievements of BPJamsostek Pasuruan Pandaan employees by implementing Work At Office (WAO) and Work From Home (WFH).The method in this research uses qualitative research, with the data analysis technique used in this research being descriptive analysis.